Pediatric Hearing Aid Use: Factors and Challenges - Salamatmanesh, Mina (Université d'Ottawa / University of Ottawa, 2021)
BACKGROUND: Population-based universal newborn hearing screening (UNHS) has been widely implemented in the developed world to ensure early detection of permanent hearing loss (HL) and improve the quality of speech and language outcomes of children with HL. Full-time hearing aid (HA) use is crucial for successful early intervention; most families face many challenges and uncertainties related to their child’s HA use in the early years after HA fitting. To our knowledge, there is limited information on HA use in children from Canadian settings, and there is no research using data logging records to examine a child’s HA use in the Canadian pediatric setting. GOALS: This thesis compromised three inquiries, which aimed to 1) conduct a systematic review of pediatric HA use; 2) examine HA use trends based on data logging records; 3) explore needs and challenges of HA use in young children from clinicians’ perspective. METHODOLOGY: Following a systematic review of the current literature, this doctoral research used a mixed methodology approach to examine the objectives of inquiries 2 and 3. In inquiry 2, the HA use trends in a Canadian pediatric population were explored through a retrospective chart review. In inquiry 3, the needs and challenges of HA use in the pediatric population were studied through focus group discussions with healthcare professionals involved in providing services to children with HL and their families. RESULTS: In the first inquiry (systematic review), 15 studies met the review criteria. Only four studies reported HA use based on data logging records. Age, degree of HL and parents’ education level were the most frequently reported factors associated with a child’s amount of HA use. In the second inquiry, our study sample consisted of 80 children. The study results showed an average of 7.3 hours (SD: 4.27) of HA use in the first data logging session, among all 80 cases. There was a significant association between a child’s chronological age, laterality of HL, duration of HA use and the amount of HA use. For the last inquiry, 15 clinicians from the CHEO audiology clinic participated in focus group discussion. Clinicians indicated that key items for better HA use outcomes included child-specific factors, family-related factors, and a multidisciplinary team approach. CONCLUSION: Through this research program, we confirmed various factors, including child’s characteristics, family-related factors, and a child setting, could affect a child’s average daily HA use. From this thesis, we learned that attention should be given to families' unique challenges to provide efficient solutions in an understandable format according to their specific needs and challenges. This thesis lays a foundation for future research on HA use in early childhood, one of the important factors associated with a successful early intervention program in hearing rehabilitation.
Keywords: Hearing Aid; Pediatric; Hearing Aid Use; Data Logging